Frailty and Related Factors in Hospitalized Older People in Northern Cyprus - Feray Gökdoğan; Gizem Abbasoğlu Barabar (Galenos Publishing House, 2022)
Objective:This study aimed to evaluate frailty in hospitalized older people and to identify the related factors.Method:The descriptive study was conducted on 60 older people (66-88 years) who received inpatient treatment in geriatric clinics of two hospitals between September and December 2020. Ethics committee approval, institutional consent, and informed patient consent were obtained for the study. Along with the Edmonton Frailty Scale, a data form was used to collect data about the patient's socio-demographic, disease characteristics, and frailty risk factors. The data were collected through face-to-face interviews.Results:Frailty of various levels mildly 51.6% and moderately 36.6% of the older people hospitalized in geriatric units in Northern Cyprus was detected (Edmonton Frailty Scale score of 9.23 ± 1.49). The older people in the advanced age (85 years and above) group had an even higher frailty level with the score of 10.0 (p = .009). Those who self-rated as "bad" had either a low education level, were living without a partner, had two chronic diseases, had to use four to seven drugs daily, had a health problem within the last 15 days, had to visit the hospital in the last year, or had to be hospitalized, and had higher min-max Edmonton Frailty Scale scores (p > .05).Conclusion:The frailty levels in older people hospitalized in geriatric units were found to be higher. The older people were classified as frail because of the number of frailty risk factors such as weight loss, weakness, lack of appetite, or had more than three falls.